The epic towns project – a presentation - Detelić, Mirjana (Zeitschrift für Balkanologie, 2003)
Supported by FOSYU and Serbian Ministry of Science and Technologies, the Institute for Balkan Studies started a new project titled The Image and Concept of Towns in Christian and Moslem Epic Ballads. The team engaged on it consists of the researchers of different profiles – literary scholars, linguists, etymologists, historians, cartographers, geographers, and others. Its objective is to present the results of this team-work in both electronic and standard ways: as a CD-Rom (with Web presentation) and as a printed monograph. The principal researcher of the project is Dr. Mirjana Detelić. The project will deal with the best, classical published collections of oral epic ballads from Croatia, Bosnia, Herzegovina, Montenegro, and Serbia. The sample thus formed comprehends about 1500 songs of the highest literary value, emphasizing by the mese siye of it its high scientific reliability and relevance. This exclusively literary material is nevertheless a source of different kinds of data and, for that reason, will be processed multidisciplinary as a special kind of database. The choice of material for this investigation arises from the conceptualization of urban space within epic poetry, because of its strong ideological position as a human habitation clearly defined in time and space. The Epic Towns Project is divided in five parts: Introductory essay/study; Lexicon of towns and other inhabited places (with two browse modes: by name of a place and by its attribute); Tabular presentation of the material (with two browse modes: by juxtaposition and linear); Maps (approx. 1500, one for each poem, representing its spatial image); Corpus (the epic ballads themselves). The lexicon will occupy the central part of both the CD and the book. It will cover for all the inhabited places mentioned in the ballads and will consist of approximately 900 units. The sort and scope of information it will carry can be presented by this sample: AVALA  Žrnov, Žrnovan  Havala – tur.: a place, a hill which dominates the surroundings; Havale – arab.: a hill, a high spot; a fortress which dominates a city is often called thus.  Old Serbian. Žrьnovь, Žrьnovanь, ŽrьvovanьXV c. (DAN.), probably according to the mill stone: common Slavonic *žьrnu, žьrnve, SC. žrvanj (SKOK III 685 sq.). Više Bi(j)ograda: U Avali više Bijograda (Vuk II,93); Na Avalu više Biograda (MH III,1:695) Iznad Bijograda: Sa Avale iznad Bijograda (Vuk IV, 46) Without attribute: Na Avalu do Porčine kule (KH I,4), Sa Avale kad topuz otisne (MH III, 1:703) Turkish name for an old town called Žrnov or Žrnovan, south from Belgrade. For some time, at the beginning of their rule, Turks also used to call it Gözelce (gözel = beautiful). After the Turks occupied Serbia and unsuccessfully attacked Belgrade in 1440, the Žrnov town was under Hungarian rule. When the Turkish army invaded Erdely (Transylvania) in 1442, major parts of Hungarian military left the town, so Turks got their chance and took it back. They renovated the town after the unsuccessful siege of Belgrade in 1458, and named it Avala, or Havale, which means: the checkpoint, a fortress dominating another fortress or a city. „From the ruins of the little medieval town Žrnov, which they called Avala, Turks built a real brigand’s tower, covered with lead. From there, they ruled the surroundings of Belgrade, which they literally devastated.“* This Turkish town is also mentioned in the old Serbian written sources: in the year 1515, May 6th „Balil beg broke the Erdely duke Janoš at Havala“.** After the fall of Belgrade in 1521, the town of Avala lost its former significance and finally was abandoned in XVIII century. The ruins of the town were visible at the mount Avala till 1934, when they were destroyed to make place for a monument of the unknown soldier 1914–1918. According to Evly Cheleby, the epic hero Porča of Avala was a historical personality who lived there in XV century. Yet another medieval town Havala exists in Bosnia, on the banks of the river Una, above Kulen-Vakuf in direction of the Old Ostrovica. It was built in the time of the sultan Ahmed III (1703-1730). Bibliography: DANIČIĆ 1, p. 342; 3, p. 406**; DEROKO 1950, p. 101–102; EČ 329, n. 18, 24; RADONIĆ I – 82, n. 51; NIKOLIĆ 1903, p. 907*; Vojna enciklopedija, s.v. Avala; Grad. The special advantage of its electronic edition is to add maps of the events described in ballads and the texts themselves, which will enable its more complex and easier use for different purposes – at schools as well as for individual scientific research or entertainment.